Mutu Layanan Pendidikan di SMP Assa’adah Kecamatan Duren Sawit Jakarta Timur - Muhammad Nukman; Supadi Supadi; Siti Zulaikha (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
The research was conducted in Assa’adah Junior High School District DurenSawit East Jakarta, which aims to identify and obtain an overview of the quality ofeducational services. This research was conducted in October 2016 until February 2017.approach used is qualitative approach with methods descriptions. Data collection wasdone through interviews, observation and documentation. source data from this study isthe principal and several supporting informant as deputy principals and heads ofadministration. Based on the results of research and data analysis, it can be concludedthat the quality of service at Assa’adah Junior High School has been running well. then,from the quality of the services performed directly supervised by the principal. it can beseen from the quality planning services starting from problem analysis, identification ofneeds, formulation of objectives, devise alternative actions, action selection, preparationof work plans, implementation of the work plan, evaluation, and feedback. Furthermore,quality control process of comparing the performance of the service begins with thetarget of evaluation, problem analysis, and manufacture of alternative actions. then, thestrategy of increasing the quality of services consisting of the development of educators,improved quality of service, and continuous improvement.